Analysis Tool for Radar Data Using C‘ Oriented Approach (International Journal of Engineering and Computer Science, 2013)
The main objective of our project Radar Data Analysis Tool an ‘C’ oriented approach scan the tracking data sent to mission computers by Radars like PCMC’S and RADAR’S. The Radar emits signals continuously towards the target. These signals strike the target and echoes (reflects) back towards the radar. The Radar generally equipped with Data System. This system gathers tracking information of the target such as Range, Elevation, and Azimuth individually from various sub systems of radar. This data is transmitted at 10 Hz rate to the mission computers for processing. Check for the validity of scanned tracking data. Arranged data into various data formats such as 22-Bytes, 18-Bytes etc according to various radars. Display the data formats in Hexadecimal form. Plot the graph for prime parameters acquired through data packers.